Evolutionary Engineering in Chemostat Cultures for Improved Maltotriose Fermentation Kinetics in Saccharomyces pastorianus Lager Brewing Yeast - Brickwedde, Anja; van den Broek, Marcel; Geertman, Jan-Maarten A.; Magalhães, Frederico; Kuijpers, Niels G. A.; Gibson, Brian; Pronk, Jack T.; Daran, Jean-Marc G. (Frontiers in Microbiology, 2017)
The lager brewing yeast Saccharomyces pastorianus, an interspecies hybrid of S. eubayanus and S. cerevisiae, ferments maltotriose, maltose, sucrose, glucose and fructose in wort to ethanol and carbon dioxide. Complete and timely conversion (‘attenuation’) of maltotriose by industrial S. pastorianus strains is a key requirement for process intensification. This study explores a new evolutionary engineering strategy for improving maltotriose fermentation kinetics. Prolonged carbon-limited, anaerobic chemostat cultivation of the reference strain S. pastorianus CBS1483 on a maltotriose-enriched sugar mixture was used to select for spontaneous mutants with improved affinity for maltotriose. Evolved populations exhibited an up to five-fold lower residual maltotriose concentration and a higher ethanol concentration than the parental strain. Uptake studies with 14C-labelled sugars revealed an up to 4.75-fold higher transport capacity for maltotriose in evolved strains. In laboratory batch cultures on wort, evolved strains showed improved attenuation and higher ethanol concentrations. These improvements were also observed in pilot fermentations at 1000-L scale with high-gravity wort. Although the evolved strain exhibited multiple chromosomal copy number changes, analysis of beer made from pilot fermentations showed no negative effects on flavour compound profiles. These results demonstrate the potential of evolutionary engineering for strain improvement of hybrid, alloploid brewing strains.